God, grace, and righteousness in wisdom of Solomon and Paul's letter to the Romans : texts in conversation - Linebaugh, Jonathan A. (Supplements to Novum Testamentum ;, 2013)
In God, Grace, and Righteousness in Wisdom of Solomon and Paul's Letter to the Romans, Jonathan A. Linebaugh places the Wisdom of Solomon and the Letter to the Romans in conversation.